2021
DOI: 10.1177/15248380211032213
|View full text |Cite
|
Sign up to set email alerts
|

PTSD in the Year Following Sexual Assault: A Meta-Analysis of Prospective Studies

Abstract: Objective: Sexual assault is associated with higher rates of posttraumatic stress disorder (PTSD) than other traumas, and the course of PTSD may differ by trauma type. However, the course of PTSD after sexual assault has not been summarized. The aim of this meta-analysis was to identify the prevalence and severity of PTSD and changes to the average rate of recovery in the 12 months following sexual assault. Method: Authors searched four databases for prospective studies published before April 2020 and sought r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 82 publications
6
55
0
Order By: Relevance
“…Our second research question addressed the probability of transitioning from one latent class into another over a 1-year period. Consistent with Dworkin et al’s (2021) findings that many sexual assault survivors report decreases in distress over time, our results indicated that 42–66% of participants in each latent class de-escalated into a lower severity class between Time 1 and Time 2. Because participants assigned to the highest severity class at Time 1 had no possibility of escalation and participants assigned to the lowest severity class at Time 1 had no possibility of de-escalation, the stability of these classes also informs the interpretation of escalation and de-escalation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our second research question addressed the probability of transitioning from one latent class into another over a 1-year period. Consistent with Dworkin et al’s (2021) findings that many sexual assault survivors report decreases in distress over time, our results indicated that 42–66% of participants in each latent class de-escalated into a lower severity class between Time 1 and Time 2. Because participants assigned to the highest severity class at Time 1 had no possibility of escalation and participants assigned to the lowest severity class at Time 1 had no possibility of de-escalation, the stability of these classes also informs the interpretation of escalation and de-escalation.…”
Section: Discussionsupporting
confidence: 89%
“…There are important areas for expansion within the wider sexual assault and PTSD literature as well. Dworkin’s (2021) meta-analysis found that 40% of U.S. studies on PTSD after sexual assault were based on samples at least two-thirds White, highlighting a need for PTSD research to be carried out with racially diverse samples. Additionally, much of the literature on sexual assault survivors’ experiences of PTSD is based on samples in the immediate aftermath of an assault (Armour et al, 2012; Dworkin et al, 2021; Steenkamp, Dickstein, et al, 2012).…”
mentioning
confidence: 99%
“…Similarly, sexual abuse as a traumatic experience has been reported by other authors [ 60 , 61 ] and related to PTSD symptoms. Results of a meta-analysis reported that 75% of sexual assault survivors met the criteria for PTSD after one month [ 62 ]. One explanation for this phenomenon in perinatal period is that pregnancy and delivery process may activate the woman’s experiences of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is possible that less frequent discussion limits the recipient’s ability to process what happened to the victim leading to less confidence in their ability to help the victim. The finding that disclosure recipients perceived less victim blame when the DSV occurred longer ago compared to more recently could be due to the fact that victims are likely more distressed regarding recent DSV (Dworkin et al, 2021). This could lead a disclosure recipient to feel a greater need to help the victim leading to increased burden.…”
Section: Discussionmentioning
confidence: 99%